Promoted Photocatalytic Hydrogen Evolution by Molecular Ring‐Substituting Doping and Regulation of Charge Carrier Migration in Graphitic Carbon Nitride. Issue 7 (6th April 2018) - Yan, Wei; Yu, Yu; Zou, Haihan; Wang, Xiaofang; Li, Pei; Gao, Wenyu; Wang, Junzhong; Wu, Songmei; Ding, Kejian
Abstract : The recombination of photo‐induced carriers is one of the most fatal restrictions in the high performance of many photocatalysts including graphitic carbon nitride (g‐C3 N4 ). By employing a benzene‐based co‐monomer with the substituents in the matched positions during the thermal‐polymerization, a molecular ring‐substituting doping is successfully realized. The excited electrons and holes under the photo‐irradiation could be regulated into different sections in the crystal by the improved electronic structure. The light absorption, separation of photo‐generated carriers, and electroconductivity are all significantly enhanced in the modified photocatalyst. This substituting doping strategy at molecular level endowed the photocatalyst with an extraordinarily aggrandized hydrogen evolution rate (nearly 12 times), as well as a high stability. Abstract : A molecular ring‐substituting g‐C3 N4 structure is prepared by using a benzene‐based derivate with the substituents in the matched positions as a co‐monomer. The improved electronic structure can regulate the excited electrons and holes into different crystal sections. The simultaneously improved light absorption and electroconductivity extraordinarily enhanced the photocatalytic hydrogen evolution rate (nearly 12 times).